Animation for beginners : getting started with animation filmmaking - Meroz, Morr (Bloop Animation Studios LLC, 2021)
"If you are an aspiring animator considering a career in film production or are curious about what it takes to make animated shorts, this is the book for you! Animation for Beginners is a comprehensive and modern introduction to the art and business of 3D animation from Bloop Animation founder, filmmaker, graphic novel author, and teacher Morr Meroz."--Back cover.